2001
DOI: 10.1086/320118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutations in the CPO Gene in British Patients Demonstrates Absence of Genotype-Phenotype Correlation and Identifies Relationship between Hereditary Coproporphyria and Harderoporphyria

Abstract: Hereditary coproporphyria (HCP) is the least common of the autosomal dominant acute hepatic porphyrias. It results from mutations in the CPO gene that encodes the mitochondrial enzyme, coproporphyrinogen oxidase. A few patients have also been reported who are homoallellic or heteroallelic for CPO mutations and are clinically distinct from those with HCP. In such patients the presence of a specific mutation (K404E) on one or both alleles produces a neonatal hemolytic anemia that is known as "harderoporphyria"; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 37 publications
2
49
0
1
Order By: Relevance
“…Three previously reported polymorphisms, 814A/C (exon 4), 880G/A (exon 4), and 990G/A (exon 5) (Fujita et al 1994;Lamoril et al 2001;Martasek et al 1994b;Petersen et al 2000;Sassa et al 1997) were identified among the investigated individuals. The frequency of these alleles in the control individuals were 0.87A/0.13C (814), 0.94G/ 0.06A (880), and 0.72G/0.28A (990).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Three previously reported polymorphisms, 814A/C (exon 4), 880G/A (exon 4), and 990G/A (exon 5) (Fujita et al 1994;Lamoril et al 2001;Martasek et al 1994b;Petersen et al 2000;Sassa et al 1997) were identified among the investigated individuals. The frequency of these alleles in the control individuals were 0.87A/0.13C (814), 0.94G/ 0.06A (880), and 0.72G/0.28A (990).…”
Section: Resultsmentioning
confidence: 60%
“…In family A, no relatives were available for investigation. In the probands of families C, D, and E, the two previously reported mutations 991CϾT (R331W, exon 5) (Lamoril et al 2001;Martasek et al 1994b) and 1339CϾT (R447C, exon 7) (Lamoril et al 2001) were shown to coexist. Investigation of the members of these three families revealed that both these mutations are located on one allele, and that they segregate with the HCP diagnosis (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Previously, determination of the diagnostic accuracy of metabolite and enzyme tests for acute porphyria has been difficult because of the absence of any method for defining groups of affected and unaffected individuals with 100% accuracy. The introduction of tests for disease-specific mutations has helped to solve this problem (5)(6)(7). A recent report in this Journal used this approach to evaluate investigations for AIP (8 ), and in this issue Hift et al (9 ) do the same for VP, capitalizing on its high prevalence in South Africa and the availability of a simple DNA test for the predominant R59W mutation.…”
mentioning
confidence: 99%